A METHOD FOR INTERACTIVE LEARNING - Pradono, Satrio; Astriani, Maria Seraphina; Moniaga, Jurike (Bina Nusantara University, 2013)
Learning methods play an important role and receive special attentions in our life. We live in digital era, where everyone wants something efficient, effective, dynamic, fast and interactive. The term ‘interactive’ appears in two distinct strands of educational research discourse: one concerning pedagogy and the other concerning new technologies in education. Teaching students with traditional method where there is only one way of communication is no longer effective. The word interactive is the key to have an effective and efficient teaching and learning process where the teacher can grab students’ attention and students can learn more in comparison to that of the traditional method.